The Role of Artificial Intelligence in Enhancing Athlete Performance and Training Strategies - Satender Balwant Singh (Recent Trends in Sports, 2026)
Artificial Intelligence (AI) is transforming modern sports by improving athlete performance, training methods, and decision-making processes. The integration of AI technologies such as machine learning, data analytics, wearable sensors, and computer vision has enabled coaches and sports scientists to analyze large amounts of performance data with greater accuracy and efficiency. Athletes' physiological indicators, movement patterns, injury risks, and recuperation processes are all monitored by these technology. Training regimens can therefore be tailored to each athlete's unique requirements, strengths, and shortcomings. By assessing technique, speed, endurance, and tactical conduct during practice and competition, AI-based systems also help with performance analysis. Coaches can spot performance trends and make tactical changes to enhance results by using predictive analytics. In addition, AI supports injury prevention by detecting abnormal movement patterns and workload imbalances that may lead to physical strain. Real-time feedback provided through AI-enabled devices allows athletes to correct their posture and technique immediately during practice sessions. Furthermore, AI plays an important role in talent identification and scouting by analyzing performance statistics and biometric data. Sports organizations are increasingly adopting AI tools to enhance training efficiency, optimize recovery strategies, and improve overall team performance. Despite these advantages, the effective implementation of AI requires proper data management, ethical considerations, and collaboration between sports scientists, coaches, and technology experts. Overall, Artificial Intelligence has become a valuable tool in modern sports science, offering innovative solutions for performance enhancement, personalized training strategies, and evidence-based decision making in athletic development.
Keywords: Artificial intelligence; athlete performance; injury prevention; machine learning; performance monitoring; sports analytics; sports technology; training strategies